2017
DOI: 10.3897/zookeys.688.12636
|View full text |Cite
|
Sign up to set email alerts
|

Stranding survey as a framework to investigate rare cetacean records of the north and north-eastern Brazilian coasts

Abstract: Marine mammal stranding events are used as an important tool for understanding cetacean biology worldwide. Nonetheless, there are vast gaps of knowledge to be filled in for a wide range of species. Reputable information is required regarding species from large baleen whales to sperm and beaked whales, as well as pelagic dolphins. This paper describes new cetacean records from north and north-eastern Brazil, which are both the least surveyed areas regarding aquatic mammals. Regular beach surveys were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
4
12
0
1
Order By: Relevance
“…Strandings were diffusely distributed along the Espírito Santo coast, without well-defined hotspots. The number of strandings of this species in this study was relatively high compared to similar surveys conducted in other portions of the Brazilian coastline ( Prado et al 2016 , Vianna et al 2016 , Costa et al 2017 ), which is consistent with at-sea surveys showing that melon-headed whales are occasionally seen along the coast of Espírito Santo ( Wedekin et al 2009 , 2014 ). It is worth noting that there was one instance where a live individual stranded in the state, but it later died and its death was attributed to plastic ingestion ( Costa et al 2012 ), illustrating the impacts of plastic pollution can have on this species.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Strandings were diffusely distributed along the Espírito Santo coast, without well-defined hotspots. The number of strandings of this species in this study was relatively high compared to similar surveys conducted in other portions of the Brazilian coastline ( Prado et al 2016 , Vianna et al 2016 , Costa et al 2017 ), which is consistent with at-sea surveys showing that melon-headed whales are occasionally seen along the coast of Espírito Santo ( Wedekin et al 2009 , 2014 ). It is worth noting that there was one instance where a live individual stranded in the state, but it later died and its death was attributed to plastic ingestion ( Costa et al 2012 ), illustrating the impacts of plastic pollution can have on this species.…”
Section: Discussionsupporting
confidence: 90%
“…At-sea observations suggest that sperm whales tend to concentrate along the central coast of Bahia, especially at the Camamu-Almada Basin, and occur at much lower densities in Espírito Santo (Batista et al 2012). The number of strandings of this species in this study was relatively high compared to similar surveys conducted in other portions of the Brazilian coastline (Prado et al 2016, Vianna et al 2016, Costa et al 2017, which suggests this species probably forages along the Vitória-Trindade ridge and occasionally approaches the Espírito Santo coast. It is worth noting that previous studies suggested that the species might be most abundant in Espírito Santo waters in winter and spring, from July to November (Batista et al 2012), but this was not evident in the strandings recorded in this study.…”
Section: Sperm Whale Physeter Macrocephalus Linnaeus 1758supporting
confidence: 39%
See 2 more Smart Citations
“…A large proportion of what is known about cetaceans in Brazilian waters comes from studies using dead individuals collected from stranding events (e.g. Zerbini et al 1997, Greig et al 2001Ramos et al 2001, Costa et al 2017 and/or incidental catches in fishing operations conducted since the end of the 1970s (e.g. Siciliano 1994).…”
Section: Introductionmentioning
confidence: 99%